2018
DOI: 10.4236/jbm.2018.610002
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Sodium Was Prepared from Pig Intestinal Mucosa by Dialysis and Spray Drying

Abstract: A method to extract crude heparin sodium from pig intestinal mucosa by dialysis and spray drying was established. The pig intestinal mucosa was treated in the following steps: enzymolysis, resin exchange adsorption-washing, elution, pressure filtration, dialysis, spray drying. Activity of the product was measured using a heparin anti-IIa factor assay kit. The yield of crude heparin obtained by this method was 2.79% higher than that of oven drying method; the production of 1 kg crude heparin sodium saved 43.4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“… 3 One pig yields approximately 650 mg of crude heparin containing about 65,000 IU of both antifactor IIa and antifactor Xa activity. 4 Therefore, based on the usual heparin dose of 5000 IU of unfractionated heparin or 5000 IU of dalteparin, a low molecular weight heparin, 1 pig has to be slaughtered per 13 dialysis sessions. The carbon footprint of raising 1 pig is about 670 kg CO 2 equivalent, which poses a serious threat to the external environment.…”
Section: Discussionmentioning
confidence: 99%
“… 3 One pig yields approximately 650 mg of crude heparin containing about 65,000 IU of both antifactor IIa and antifactor Xa activity. 4 Therefore, based on the usual heparin dose of 5000 IU of unfractionated heparin or 5000 IU of dalteparin, a low molecular weight heparin, 1 pig has to be slaughtered per 13 dialysis sessions. The carbon footprint of raising 1 pig is about 670 kg CO 2 equivalent, which poses a serious threat to the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…The other types of resins were successfully employed in heparin separation such as D254 resin (Shu et al, 2018) and Q-Sepharose (method of Volpi, Sarwar et al, 2015). The comparative study of adsorption performance of quaternized-CS/PS microbeads, CS/PS microbeads and Amberlite FPA98 Cl resin showed that the quaternized-CS/PS microbeads had a better adsorption performance than others (Eskandarloo et al, 2018).…”
Section: Heparin Isolationmentioning
confidence: 99%